2019
DOI: 10.1016/j.oregeorev.2019.02.032
|View full text |Cite
|
Sign up to set email alerts
|

From Mantle to Motzfeldt: A genetic model for syenite-hosted Ta,Nb-mineralisation

Abstract: A genetic model for the Motzfeldt Tantalum-Niobium-rich syenite in southwest Greenland, considered to be one of the world's largest Ta prospects, is presented. The Motzfeldt primary magma formed early in regional Gardar (1273±6 Ma) rifting. Isotope signatures indicate that the Hf had multiple sources involving juvenile Gardar Hf mixed with older (Palaeoproterozoic or Archaean) Hf. We infer that other High Field Strength Elements (HFSE) similarly had multiple sources. The magma differentiated in the crust and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…In brief, Ilímaussaq hosts agpaitic nepheline syenites (peralkaline rocks with complex Na-Ca-HFSE minerals) and is one of the most reduced and chemically evolved magmatic series known 43 . Motzfeldt predominantly hosts miaskitic nepheline syenites (peralkaline rocks with zircon and Fe-Ti oxides), which formed at reduced magmatic conditions (less extreme than Ilímaussaq, but still below the QFM buffer 40 ) and underwent intense late-stage oxidation 44 . Ivigtût is an alkaline granite stock that is associated with the world’s largest deposit of cryolite (Na 3 AlF 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In brief, Ilímaussaq hosts agpaitic nepheline syenites (peralkaline rocks with complex Na-Ca-HFSE minerals) and is one of the most reduced and chemically evolved magmatic series known 43 . Motzfeldt predominantly hosts miaskitic nepheline syenites (peralkaline rocks with zircon and Fe-Ti oxides), which formed at reduced magmatic conditions (less extreme than Ilímaussaq, but still below the QFM buffer 40 ) and underwent intense late-stage oxidation 44 . Ivigtût is an alkaline granite stock that is associated with the world’s largest deposit of cryolite (Na 3 AlF 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…If natural pyrochlores contain a lot more U than Th (e.g. [ 15 ]) then either the melt must have had exceptionally high U/Th [ 52 ], or, perhaps more common, the pyrochlores were precipitated from or altered by a hydrothermal fluid, which can transport U much more efficiently than Th [ 15 ]. A recent paper shows nicely how the U and Th composition of pyrochlore varies with increasing degree of alteration: Whereas primitive pyrochlores contain wt.% of Th and only little U, the U content of pyrochlore increases and the Th content decreases with increasing degree of hydrothermal alteration [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we focus on the Nb-and Ta-rich accessory phases pyrochlore, microlite, and fersmite, which are accessory phases in alkaline silicate rocks [14][15][16][17][18][19][20] and, perhaps more commonly, carbonatites [18,[21][22][23]. Note that these mineral phases are the most important hosts for Nb and Ta in ore deposits (e.g., [18,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…There is a current controversy over the role that magmatism and post‐magmatic alteration play during HFSE and REE mineralization in alkaline igneous rocks. On the one hand, certain studies suggest that magmatism caused the formation of these deposits (Finch et al, ; Huang, Wang, Zhang, Li, & Qin, ; Huang, Zhang, Santosh, & Zhang, ; Kogarko, ; Kovalenko et al, ; Linnen & Keppler, ; Mccreath, Finch, Herd, & Armour‐Brown, ). On the other hand, studies have suggested that a combination of magmatism and post‐magmatic alteration resulted in the formation of these deposits (Kempe, Götze, Dandar, & Habermann, ; Salvi & Williams‐Jones, , , ; Schmitt, Trumbull, Dulski, & Emmermann, ; Sheard, Williams‐Jones, Heiligmann, Pederson, & Trueman, ; Wang, Zhao, & Chen, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Khaldzan‐Buregtey Zr–Nb–REE deposit contains mineralization distributed in albitized, silicified, and epidotized igneous rock (Kovalenko et al, ). The majority of the pyrochlore in the Motzfeldt syenite‐hosted Nb–Ta deposit has a metamorphic structure (Finch et al, ; Mccreath et al, ). Post‐magmatic alteration, especially albitization and greisenization, in the Boziguo'er rare metal granite is ubiquitous (Huang et al, , ).…”
Section: Introductionmentioning
confidence: 99%